Pengaruh Perbandingan Tepung Sukun (Artocarpus altilis) dan Tepung Labu Kuning (Cucurbita moschata) Terhadap Karakteristik Brownies Kukus - Primsa Ginting, Mia; Suparthana, I Putu; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPA, 2023)
This study aimed to determine the effect of breadfruit flour and pumpkin flour composition on the characteristics of brownies, and to get the best composition which resulting in the best characteristic of the brownies. The experiment was designed as a completely randomized design with breadfruit flour and pumpkin flour composition used as the treatments, those consisting of 5 treatment levels, namely: P0 (100%: 0%), P1 (90%: 10%), P2 (80%: 20%), P3 (70%: 30%), and P4 (60%: 40%). Each treatment was repeated 3 times to obtain 15 experimental units. The data were analyzed by using analysisof variance and for the treatment showed significant effect, it continues analized by using Duncan Multiple Range Test. Theresults showed that ratio of breadfruit flour and pumpkin had a significant effect (P<0,05) on ash content, protein content,fat content, crude fiber content, beta carotene content, aroma, taste, texture, color, and overall acceptability, however it did not affect the moisture content. The ration of breadfruit flour (60%) and pumpkin flour (40%) produced the best characteristics of brownies with water content of 24.42%, ash content of 2.28%, protein content of 9.54%, fat content of 21.09%, carbohydrate content of 42.29%, crude fiber content of 4.06%, beta carotene content of 6.27 mg/100g. Thesensory characteristics were hedonic color of color 0f 4.35, aroma of 4.70, texture of 4.50, and taste of 4.75. Scoring color of 2.80, aroma of 2.90, texture of 2.85, and taste 0f 2.90.